The Conservative Party Leadership Election of 2016: An Analysis of the Voting Motivations of Conservative Parliamentarians. Issue 2 (28th August 2017) - Jeffery, David; Heppell, Tim; Hayton, Richard; Crines, Andrew
Abstract: This article provides the first systematic examination of the voting motivations of Conservative MPs in the final parliamentary ballot of the Conservative Party leadership election of 2016. We identify the voting behaviour of each Conservative parliamentarian as part of a unique data set that we use to test, through the use of multivariate analysis, a series of hypotheses based around social background variables (i.e. gender and education); political variables (i.e. parliamentary experience, electoral marginality, the electoral threat posed by UKIP and ministerial status); and ideological variables (i.e. attitudes towards same-sex marriage and Brexit). Our findings demonstrate that ideology did matter in terms of voting. Attitudes towards Brexit were central to the appeals of both Theresa May (to Remainers) and Andrea Leadsom (to Leavers). We also demonstrate that in terms of support for Leadsom, Brexit was not the only significant driver, as opinion on same-sex marriage, year of entry and ministerial status also influenced voting behaviour.